2022
DOI: 10.4049/immunohorizons.2100107
|View full text |Cite
|
Sign up to set email alerts
|

Selective Pharmaceutical Inhibition of PARP14 Mitigates Allergen-Induced IgE and Mucus Overproduction in a Mouse Model of Pulmonary Allergic Response

Abstract: The type 2 cytokines IL-4 and IL-13, which share use of an IL-4 receptor a-chain and its nuclear induction of the transcription factor STAT6, are crucial in elicitation and maintenance of allergic conditions including asthma. STAT6 binds poly(ADP-ribose) polymerase (PARP)14, an ADP-ribosyl monotransferase. Elimination of PARP14 by gene targeting led to attenuation of OVA-specific allergic lung inflammation. However, PARP14 has multiple functional domains apart from the portion that catalyzes ADP-ribosylation, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
1
2
0
Order By: Relevance
“…These motifs are present in the promoter region of interleukin-4 (Il-4) and Il-5 and PARP14 seems to have a role in the expression of T helper type 2 (Th2) cytokines [ 120 ]. This is further supported by findings of a role of PARP14 in allergic reactions in mice [ 121 ].…”
Section: The Ifn-regulated Subclass Of Parpssupporting
confidence: 72%
“…These motifs are present in the promoter region of interleukin-4 (Il-4) and Il-5 and PARP14 seems to have a role in the expression of T helper type 2 (Th2) cytokines [ 120 ]. This is further supported by findings of a role of PARP14 in allergic reactions in mice [ 121 ].…”
Section: The Ifn-regulated Subclass Of Parpssupporting
confidence: 72%
“…First of all, these studies are fuelled by the genetic findings where body-wide deficiency of Parp14 in mice diminished the intensity of allergic reactions 11,12,34 . To this end, one ART activity inhibitor was recently shown to reduce pulmonary allergic response in mice 35 and one ART activity inhibitor entered clinical trials in atopic dermatitis (Phase I, NCT05215808). Secondly, in vitro genetic findings have demonstrated that Parp14 inactivation in macrophages skews them toward a pro-inflammatory IFN-γ-driven M1 phenotype while reducing the IL-4-driven M2 phenotype 13 .…”
Section: Discussionmentioning
confidence: 99%
“…First of all, these studies are fueled by the genetic findings that a body‐wide deficiency of Parp14 in mice diminished the intensity of allergic reactions 11,12,47 . To this end, one ART activity inhibitor was recently shown to reduce pulmonary allergic response in mice 48 and one ART activity inhibitor entered clinical trials for atopic dermatitis (Phase I, NCT05215808). Secondly, in vitro genetic findings have demonstrated that Parp14 inactivation in macrophages skews them toward a pro‐inflammatory IFN‐γ‐driven M1 phenotype while reducing the IL‐4‐driven M2 phenotype 13 .…”
Section: Discussionmentioning
confidence: 99%